Novel insights into the inhibitory mechanism of (+)-catechin against trimethylamine-N-oxide demethylase. (30th March 2022) - Li, Yingchang; Song, Suzhen; Li, Yuanyuan; Du, Fengxia; Li, Shuangyan; Li, Jianrong
Highlights: The molecular mass of TMAOase was 25 kDa. (+)-Catechin suppressed the activity of TMAOase in a reversible non-competitive inhibition type. The quenching mechanism of (+)-Catechin against TMAOase is static quenching. Circular dichroism results showed that secondary structure of TMAOase is altered by (+)-Catechin. Abstract: Trimethylamine- N -oxide demethylase (TMAOase) is a key enzyme for the decomposition of trimethylamine oxide into formaldehyde. The study investigated the inhibitory effects of (+)- catechin on TMAOase and involved mechanism to minimize the formaldehyde (FA) content of seafood during storage. TMAOase was purified by DEAE-52 cellulose and Sephacryl S-300 chromatography and the inhibitory mechanism of TMAOase was studied by Lineweaver-Burk plots, fluorescence spectroscopy, and circular dichroism. Specific activity of 37 ± 0.7 U/mg was obtained with 205 -fold purification and 15% yield, and molecular mass was 25 kDa. (+)-Catechin was a reversible inhibitor of TMAOase and its induced mechanism was the non-competitive inhibition type. (+)-Catechin binding to TMAOase formed a complex with the binding constant (Ksv ) of 0.72 × 10 3 at 298 K. The formation of complex induced the static fluorescence quenching and changes in the conformation of TMAOase, leading to a reduction in the rate of catalysis.